1995
DOI: 10.1891/0047-2220.26.2.17
|View full text |Cite
|
Sign up to set email alerts
|

The Paradoxical Nature of Disability Services: Illustrations from Supported Employment and Implications for Rehabilitation Counseling

Abstract: Paradoxes are common in disability services and present challenges for rehabilitation counseling. Failure to reveal and address both poles of paradoxes can result in unintended consequences. The concept of paradox is illustrated in supported employment. The following two paradoxes are discussed: (a) organizational productivity versus supported employee self-actualization, and (b) support organization survival and profit versus supported employee independence and interdependence. Implications for rehabilitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Second is commodification: people with disabilities have become commodities in a disability industry (Albrecht, 1992;Szymanski & Trueba, 1994). In some cases, the independence and choice needs of people with disabilities have been pitted against the economic needs of the care-giving industry (Szymanski, Johnston-Rodriguez, Millington, Rodriguez, & Lagergren, 1995). For example, some supported employment agencies lose government subsidies when workers no longer need support.…”
Section: Challenging Policiesmentioning
confidence: 99%
“…Second is commodification: people with disabilities have become commodities in a disability industry (Albrecht, 1992;Szymanski & Trueba, 1994). In some cases, the independence and choice needs of people with disabilities have been pitted against the economic needs of the care-giving industry (Szymanski, Johnston-Rodriguez, Millington, Rodriguez, & Lagergren, 1995). For example, some supported employment agencies lose government subsidies when workers no longer need support.…”
Section: Challenging Policiesmentioning
confidence: 99%
“…Young and Murphy (2002) revealed that 74 % of disabled people not employed were unhappy; this indicated that there was a significant potential to improve further the outcomes, the majority of these people expressing a desire to be working is even more heartening. However, circumstances associated with disability may make it diffi cult for individuals to move from less to more satisfying jobs (Szymanski et al, 1995).…”
Section: Vocational Expectation and Satisfactionmentioning
confidence: 99%